Kabilin Ug Bahandi: traditional games as educational tools in the preservation of heritage and culture among universities in Cebu City - Macasil, Ma. Alena Novillo; Abrera, Maria Bernadette L. (Quezon City Asian Center, University of the Philippines Diliman, 2023)
In the modern era where technology and globalization have influenced the way individuals interact and learn, traditional games have the potential to revitalize and reinforce cultural appreciation. To validate the present corpus, the study explored to what extent universities in Cebu City in the Central Visayas region recognize the importance of traditional games as heritage (kabilin) and treasures (bahandi). The study used a qualitative approach through interpretive and phenomenological analysis to explore various roles of traditional games, in particular, how it finds their essential aspects in social construction among performers such as students, teachers, and policymakers. Traditional games were identified by students through a survey method. While the existing programs and policies of the selected institutions were identified through interviews among the incumbent and retired PE faculty and administrators. The findings show that through culturalization (pagpapasundayag) of these games, practices are continued and identities are passed down from one generation to another. For these institutions, traditional games serve as a vital medium through which cultural values such as kusog (strength), isog (resilience), and buot (character) as part of Filipino identity are recognized and valued. By examining the incorporation of these games into their curriculum, the study highlights their value in fostering cultural awareness, promoting social interaction, and enhancing learning experiences an,ong students. The elements and features of universities' practices have led to the conclusion that traditional games are important tools to develop the cultural awareness of students. Therefore integration of traditional games into curricular, cocurricular, and extracurricular activities among institutions have supplemented the effectiveness of their existing program.
Thesis (Doctor of Philosophy in Philippine Studies)--University of the Philippines Diliman
Keywords: Traditional Games -- Educational tools -- Philippines; Heritage -- Philippines; Culture -- Philippines